PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN KOLABORASI DAN HASIL BELAJAR PADA PEMBELAJARAN IPS DI SMPN 2 MOJOSARI - Ronaldo Maulana; Nuansa Bayu Segara; Wuliono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Cultural assimilation occurs when foreign cultures enter Indonesia, causing local cultures to disappear. In addition to being a popular center, foreign cultures make students less focused in receiving lessons. In addition, social studies lessons that are monotonous and use the lecture method make students not actively participate in class. This is indicated by learning outcomes that do not meet assessment completeness. Therefore, classroom action research was conducted in two cycles. The first cycle used a problem-based learning model, and the second cycle used a problem-based learning model combined with the Culturally Responsive Teaching (CRT) learning approach. The results of this study, showed that the PBL model integrated with the CRT approach improved learners' collaboration and learning outcomes and made them more active in learning because they were given contextual problems with local cultural heritage. In conclusion, the PBL model integrated with CRT approach can demonstrate the preservation of local culture in learning.